Anti-AQP4–IgG-positive Leigh syndrome: A case report and review of the literature - Chen, Jun; Wang, Jianjun; Gan, Jing; Luo, Rong; Yang, Zuozhen; Liang, Mengmeng; Chen, Xiaolu (Frontiers in Pediatrics, 2023)
Background: Leigh syndrome (LS; OMIM: 256000) is a progressive neurodegenerative disease caused by genetic mutations resulting in mitochondrial oxidative phosphorylation defects. The prognosis is poor, with most children dying before the age of two. MT-ATP6 variants are the most common mitochondrial DNA mutations in LS. MT-ATP6 variant-induced LS may trigger autoimmunity, and immunotherapy might be effective. Here, we present the first pediatric case of anti-aquaporin 4 (AQP4)–IgG-positive LS caused by an MT-ATP6 variant. Case: A 1-year-old boy was hospitalized due to recurrent fever, cough, and developmental regression. Two months before, he developed reduced responses to stimulation and psychomotor retardation. After admission, his condition deteriorated, and respiratory failure ensued. Brain magnetic resonance imaging showed symmetrical small patchy abnormal signals around the third ventricle, pons, and dorsal periaqueductal gray matter in the dorsal medulla. Laboratory tests revealed anti-AQP4–IgG antibodies. Anti-infection, immunoglobulin, and glucocorticoid therapy were administered for symptomatic treatment. Genetic testing revealed a de novo homogeneous pathogenic variant of MT-ATP6 (m.9176T>C, mutation ratio: 99.97%). The patient was diagnosed with anti-AQP4–IgG-positive LS, treated with “cocktail therapy” (vitamins B1, B2, C, and E, L-carnitine, and coenzyme Q10), and discharged after his condition improved. A literature review revealed that LS-induced mitochondrial defects can impact the immune system; hence, immunotherapy and early mitochondrial cocktail therapy may improve outcomes. Conclusion: Anti-AQP4–IgG-positive LS is very rare. LS patients with the m.9176T>C variant of MT-ATP6 may be susceptible to autoimmune damage of the central nervous system. Early cocktail therapy combined with immunotherapy may improve their prognosis.